EFEKTIVITAS RELAKSASI OTOT PROGRESIF DAN RELAKSASI NAFAS DALAM TERHADAP TEKANAN DARAH PADA KLIEN HIPERTENSI DI PUSKESMAS WONOSARI BONDOWOSO - Komariyah, Siti; Rahman, Handono Fatkhur; Tauriana, S. (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Background: Hypertension is an important health problem to pay attention to in society, because hypertension rarely causes symptoms and can kill silently. Individuals are said to be hypertensive if their systolic blood pressure is 140 mmHg or more and diastolic blood pressure is 90 mmHg or more. The number of hypertension sufferers continues to increase every year, an estimated 1.5 billion people suffer from hypertension in 2025 and an estimated 9.4 million deaths each year due to hypertension and its complications. Objective: To determine the effectiveness of progressive muscle relaxation and deep breathing relaxation on blood pressure in hypertensive clients at the Wonosari Bondowoso Community Health Center. Method: This research uses a quasi-experiment, the design used is a quasi-experimental pretest and posttest with a two group control design. Results: The results of the Wilcoxon systolic and diastolic statistical test showed that the p value was 0.000. Conclusion: There is an influence of progressive muscle relaxation and deep breathing relaxation on blood pressure in hypertensive clients. In the results of this study, there was no significant effect between progressive muscle relaxation and deep breathing relaxation